2017
DOI: 10.1002/dneu.22534
|View full text |Cite
|
Sign up to set email alerts
|

The where, what, and when of membrane protein degradation in neurons

Abstract: Membrane protein turnover and degradation are required for the function and health of all cells. Neurons may live for the entire lifetime of an organism and are highly polarized cells with spatially segregated axonal and dendritic compartments. Both longevity and morphological complexity represent challenges for regulated membrane protein degradation. To investigate how neurons cope with these challenges, an increasing number of recent studies investigated local, cargo‐specific protein sorting, and degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 176 publications
(267 reference statements)
1
49
0
Order By: Relevance
“…Preliminary studies support a potential role for glia in regulating neuronal autophagy (Alirezaei et al, 2008;Gan et al, 2012;Madill et al, 2017). Further, glial autophagy may have profound effects on neuronal function, connectivity, and response to stress induced by injury (Gomez-Sanchez et al, 2015;Jang et al, 2016;. Because many neurodegenerative diseases may propagate through a prion-like cell-to-cell transfer of disease-associated proteins (Cushman et al, 2010;Luk et al, 2012), it remains critical to define the precise role of endolysosomal trafficking and autophagy in both neurons and glia, particularly in response to neurotoxic stress (Davis et al, 2014;Melentijevic et al, 2017;Spiller et al, 2018).…”
Section: Conclusion and Future Outlookmentioning
confidence: 88%
See 1 more Smart Citation
“…Preliminary studies support a potential role for glia in regulating neuronal autophagy (Alirezaei et al, 2008;Gan et al, 2012;Madill et al, 2017). Further, glial autophagy may have profound effects on neuronal function, connectivity, and response to stress induced by injury (Gomez-Sanchez et al, 2015;Jang et al, 2016;. Because many neurodegenerative diseases may propagate through a prion-like cell-to-cell transfer of disease-associated proteins (Cushman et al, 2010;Luk et al, 2012), it remains critical to define the precise role of endolysosomal trafficking and autophagy in both neurons and glia, particularly in response to neurotoxic stress (Davis et al, 2014;Melentijevic et al, 2017;Spiller et al, 2018).…”
Section: Conclusion and Future Outlookmentioning
confidence: 88%
“…Remarkably, a number of LOAD risk variants identified through genetic screens are of genes encoding regulators of endocytic trafficking (Bertram et al, 2007;Rogaeva et al, 2007;Harold et al, 2009;Hollingworth et al, 2011;Naj et al, 2011), including Bin1 andCD2AP (Guimas Almeida et al, 2018). Using a loss-of-function approach in primary mouse cortical neurons, it was recently reported that the regulation of trafficking of APP and BACE1 through early endosomes in axons is different from dendrites.…”
Section: Endolysosomal Trafficking Of App and Bace1 And Admentioning
confidence: 99%
“…Notably, although it was widely accepted that membrane proteins were mainly degraded by endocytosis and then lysosome (e.g. LDLR and EGFR) (Beguinot et al, 1984), it has also been reported that certain membrane proteins can be degraded via autophagy, such as GABA and AMPA receptor subunits (Jin et al, 2018).…”
Section: Hfd Enhanced Akhr Accumulation By Suppressing Neuronal Autopmentioning
confidence: 99%
“…However, recent work indicates the existence of synapse‐specific mechanisms that regulate protein turnover. These may be of particular importance in the context of neurodegenerative diseases (reviewed in Vijayan & Verstreken, ; Jin et al , ) that are often characterized by misfolded, aggregated, and dysfunctional proteins [e.g., α‐Synuclein and LRRK2‐containing Lewy bodies in Parkinson's disease (PD; Spillantini et al , ; Zhu et al , )]. Neurodegeneration is often thought to start at synaptic contact sites, as these are the first cellular compartments that appear to be affected (Cheng et al , ; Burke & O'Malley, ).…”
Section: Introductionmentioning
confidence: 99%